Implementação de um cluster de alto desempenho para aplicações em engenharia - CARDOSO, Fernando Luiz de Siqueira (2019)
The UFPA Naval Engineering course was founded in 2005, through the provisional resolution of the magnificent rector of UFPA, and in 2007 with resolution 3601 was approved by the Superior Council (IES) creating the respective course, having in its curricula, materials where they teach concepts of dimensioning of ship hulls, ocean platforms, and other fields of Naval Engineering, and engineering as a whole, using software that requires high processing power. a study on the fundamental concepts of parallel computing, presenting architectures and computational models of clusters types, through a brief study on supercomputers in history, seeing their importance in scientific works and academic studies, with this, a configuration is elaborated of high-performance clustering, to be applied in software that performs various resistance calculations s of materials.